Fetal atrial flutter and hydrops successfully treated with transplacental and direct fetal therapy - Cuneo, Bettina F. (Prenatal Cardiology, 2016)
The hydropic fetus with atrial flutter has high risk of fetal demise. In utero treatment is not as successful as SVT with 1:1 conduction. Even after conversion to sinus rhythm, close follow-up of the pregnancy is required for several reasons. Case Report: A 25 year old primigravida, at 26 wks of gestation had a fetal ultrasound which showed a tachycardic hydropic fetus with AFI 49. The rhythm was atrial flutter: AR 400 bpm and VR 200 bpm. The heart was structurally normal. Transplacental antiarrhythmic treatment with sotalol was started and 24 hours later, the fetus was still primarily in flutter with rare episodes of sinus rhythm and frequent PAC. Sotalol was increased but the mother’s QTc increased to > 500 ms, so the sotalol dose was reduced. On day 4th direct i.m. of digoxin was given and fetus was in sinus rhythm. Pharmacotherapy was continued. On the 16th day of sinus rhythm (at 33 wks), a marked change in FHR variability was seen. An US revealed the fetus was in sinus rhythm with a normal FHR. Because of the decreased FHR variability, the fetus was delivered by CS and the cord pH was 7.19, Apgars 1, 9 and 9. The neonate received no antiarrhythmic medications. On day 6 of postnatal life, an AV re-entrant tachycardia ( AVRT) developed and sinus rhythm was successfully restored with sotalol and digoxin. The infant was treated for 18 months with no episodes of SVT or atrial flutter.